Veterinary Public Health Perspectives in the Slaughter of Sacrificial Animals in Bina Widya District of Municipal Pekanbaru - Handoko, Jully; Fitranda, Mulya; Anggreini, Dewi (Jurnal Veteriner dan Biomedis, 2024)
The slaughter of sacrificial animals is an annual ritual held by Muslims throughout the world which is directly associated with the potential spread of animal diseases, both non-zoonotic and zoonotic, and the threat to food safety of animal origin. This research aims to collect data from sacrificial officers in 2023 regarding the implementation of aspects of veterinary public health and animal welfare in the slaughter of sacrificial animals. A total of 58 respondents from 45 mosques in Bina Widya District, Pekanbaru City, were surveyed and interviewed purposively. The survey results show that there are two categories of field conditions, namely positive and negative categories with the negative category (72.85%) occupying the largest percentage compared to the positive category (27.15%). The t-test analysis confirmed that there was a significant difference (t statistical > t(0.95) table) between positive and negative conditions in the infrastructure aspect (3.42 > 2.13); sanitation-hygiene of sacrificial workers (6.06 > 2.13); health of sacrificial animals (4.54 > 2.13); sanitation-hygiene of meat/offal (11.15 > 2.13). Significant differences were not confirmed between positive and negative conditions from animal welfare aspects (1.66 < 2.13). Based on the analysis of the average scores, it was concluded that the infrastructure, sanitation and hygiene of sacrificial workers and sanitation and hygiene of meat/offal were in a “very poor” condition (average score < 26.84), and then the animal welfare and health aspects animals are in a “poor” condition (26.84 < average score < 33.45).